2019
DOI: 10.1111/jdv.16016
|View full text |Cite
|
Sign up to set email alerts
|

Association of combined PD‐L1 expression and tumour‐infiltrating lymphocyte features with survival and treatment outcomes in patients with metastatic melanoma

Abstract: Background Recent advances obtained with immune checkpoint inhibitors (ICIs) targeting the programmed cell death-1 (PD-1) protein have significantly improved the outcome of patients with metastatic melanoma. The PD-L1 expression in tumour cells as detected by immunohistochemistry is a predictive biomarker in some solid tumours, but appears insufficient as prognostic or predictive factor of response to ICIs in metastatic melanomas.Objectives We investigated whether the presence and the features of pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Also, the continuous anti-tumor effect of ICIs not only requires sufficient lymphocytes infiltrating in the tumor microenvironment but also depends on the high immune checkpoint expression levels of tumor cells ( 5 , 13 ). Hence, we also analyzed the relationship between HLA-DPB2/HLA-DPB1 expression and immune checkpoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the continuous anti-tumor effect of ICIs not only requires sufficient lymphocytes infiltrating in the tumor microenvironment but also depends on the high immune checkpoint expression levels of tumor cells ( 5 , 13 ). Hence, we also analyzed the relationship between HLA-DPB2/HLA-DPB1 expression and immune checkpoints.…”
Section: Discussionmentioning
confidence: 99%
“…TILs are predictive markers of the tumor-immune microenvironment and the response to ICIs therapy ( 11 ). Emerging studies have shown that the greater number of TILs, the stronger response to ICIs therapy ( 12 , 13 ). The future of immunotherapy in BC lies in the combination of ICIs with strategies that activate the immune system to pursue maximal antitumor efficacy ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In cases of multiple primary melanoma with metastases, the primary lesion should be clarified because the effect of immune checkpoint inhibitors depends on its characteristics. 5 However, if the SLN from different primary lesions are the same, as in our case, and the SLN are metastatic, the primary lesions of the metastases cannot be detected by routine examination. Therefore, in such cases, genetic analyses of LN metastases and each primary lesion should be considered to determine which primary lesion metastasized to the SLN.…”
mentioning
confidence: 60%
“…On the other hand, the prognostic value of the PD-L1 expression in patients with metastatic melanoma remains even more controversial, having been associated with better or worst prognosis in different studies [79][80][81][82][83]. Indeed, the results of 2 different studies in the adjuvant setting, one comparing nivolumab to ipilimumab and pembrolizumab to placebo, respectively, showed that recurrence-free survival was longer in patients with PD-L1 positive tumors, irrespectively from the treatment [4,84].…”
Section: Pd-1/pd-l1 Signalingmentioning
confidence: 99%